Komparasi Model Hidrolologi Runtun Waktu Untuk Analisis Hujan - Debit Menggunakan GR4J Dan Transformasi Wavelet - GR4J (Studi Kasus : DAS Indragiri Bagian Hulu) - Riady, Rony Rahmad; Fauzi, Manyuk; Suprayogi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
GR4J model is one of the well known rainfall-debit model analysis and have been successful in investigating the hydrology response of the various watersheds, espencially in indonesia. In this research is used as a case study locations are on Watershed (DAS) Indragiri Hulu section. This study used two methods, they are GR4J model and Wavelet-GR4J transformation combining method. This Wavelet-GR4J transformation Combining method is expected can increase the Nash -Sutcliffe Coefficient and the Correlation Coefficient. GR4J model used input data including daily rainfall data and at lubuk ramo station and daily potential evapotranspiration data which is the result of the CropWat program with climatology input data at sentajo station. The result of this model watershed by using debit data of daily observation at pulau berhalo station. In the next stage, calibration will be done in the certain year, verification in the next year, and simulation which is the combination of kalibration and verification. Simulation of Wavelet-GR4J Transformation resulted value equation Nash-Sutcliffe Coefficient of 12,740% and the Correlation Coefficient (R) of 0,378. In the process of Wavelet-GR4J Transformation combining method produced a better result then GR4J model based on the value of Nash-Sutcliffe Coefficient and Correlation Coefficient. The simulation of Wavelet-GR4J Transformation method resulted value equation Nash-Sutcliffe Coefficient of 12,805% and the Correlation Coefficient (R) of 0,380, it can be categorized “not sufficient” and “low” which mean that the GR4J model and the Wavelet-GR4J Transformation combining method can be said “not effective”Keywords: wavelet transformation, GR4J, calibration, verification, simulation.